2015
DOI: 10.14336/ad.2014.0623
|View full text |Cite
|
Sign up to set email alerts
|

Information Theoretical Analysis of Aging as a Risk Factor for Heart Disease

Abstract: ABSTRACT:We estimate the weight of various risk factors in heart disease, and the particular weight of age as a risk factor, individually and combined with other factors. To establish the weights we use the information theoretical measure of normalized mutual information that permits determining both individual and combined correlation of diagnostic parameters with the disease status. The present information theoretical methodology takes into account the non-linear correlations between the diagnostic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Increased age is the predominant risk factor for several major human pathologies, including cancer, diabetes, cardiovascular disease and neurodegeneration [ 1–5 ]. Long considered an inevitable consequence of life, recent advances have revealed that aging has an underlying biological process, influenced by both genetic and environmental factors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased age is the predominant risk factor for several major human pathologies, including cancer, diabetes, cardiovascular disease and neurodegeneration [ 1–5 ]. Long considered an inevitable consequence of life, recent advances have revealed that aging has an underlying biological process, influenced by both genetic and environmental factors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients' age could also be a factor. As one of the biomarkers of CVDs, age has the highest effect on CVDs' progression among the non-specific parameters (10). It is obvious that the risk of developing and sustaining CVDs increases with age (1) and this issue illustrates the necessity of study-ing the views and attitudes of patients of various ages on their disease.…”
Section: Introductionmentioning
confidence: 99%
“…Individual biomarkers may not be indicative of the process or state of degeneration, and need to be considered in combinations, or ideally in a systemic balanced way - otherwise interventions on particular biomarkers and pathways may exacerbate other biomarkers and pathways, and disrupt the system as a whole. The general methodology for the evaluation of the effects of multiple risk factors (including biomarkers of aging) on multiple age-related diseases (multimorbidity) need to be improved, to allow the evaluation of non-linear, cumulative or synergistic effects [ 31 , 42 , 43 ].…”
Section: Methodological Challengesmentioning
confidence: 99%